Same-plant trends in capacity factor and heat rate for US power plants, 2001–2018. (1st October 2020) - Grubert, Emily
Abstract: This note uses electricity generator level 2001–2018 US capacity, generation, and heat input data to evaluate trends in same-plant capacity factor (how much plants run) and heat rate (how efficiently plants run) as plants age. Based on compound annual growth rates for capacity factor and, for thermal plants, heat rate, and based on the subset of US plants that have been operating since 2010 or earlier, same-plant capacity factors increased slightly, and heat rates decreased slightly, between 2001–2018 (weighted average based on 2018 plant capacity). Trends vary by region, fuel, and plant age. Notably, US natural gas-fired power plants tended to run more, and more efficiently, as they aged, while coal-fired power plants tended to run less, and less efficiently. Potential drivers include relative plant age, policy, financial competitiveness, and an anticipated tendency for plant operators to react to the effects of equipment aging with maintenance, repair, replacement, and optimization. These observations can inform committed emissions-based research, which requires making assumptions about how plant operational characteristics change (or do not) as they age.